Electrode metallization for scaled perovskite/silicon tandem solar cells: Challenges and opportunities. (25th October 2021) - Rehman, Atteq ur; Van Kerschaver, Emmanuel P.; Aydin, Erkan; Raja, Waseem; Allen, Thomas G.; De Wolf, Stefaan
Abstract: Monolithic perovskite/silicon tandem solar cells have the potential to reach very high power conversion efficiencies ( PCE s) in a cost‐effective manner. In the last decade, significant technological advancements have been made for lab‐scale devices (~1 cm 2 ), with PCE s now higher than the theoretical PCE limit of single‐junction silicon solar cells. For market entry of such tandems, the involved processing steps need to be scaled to industrial wafer dimensions, typically >244 cm 2, which also mandates the development of adequate electrode‐metallization strategies. Here we discuss challenges and opportunities related to this, including the required properties of the front metal grid for perovskite/silicon tandems, as well as key motivations and challenges in adopting screen‐printed metallization, which is the current standard for mainstream silicon solar cells. We give a cost estimation for the front metal grid by considering the cost of low‐temperature metal pastes that are compatible with the thermal budget limitations imposed by the perovskite top cell. We also consider opportunities to employ alternative metallization schemes that arise from the reduction in current density in tandem solar cells compared to single‐junction devices. Lastly, we discuss possible routes to replace or minimize the silver content in costly silver‐based metallization for industrial applications. Abstract : Challenges and opportunities related to large area electrode metallization of perovskite/silicon tandems are discussed with focus grid design at the front. Key motivations and challenges in adopting standard screen‐printed metallization, along with cost estimations that consider the cost of low‐temperature metal pastes, are discussed. Alternate metallization routes to replace or reduce the costly silver content of printed pastes are also studied.